Brazil, Mirror of Cape Verde: the case of the São Vicente carnival - Daun e Lorena, Carmo (Revista Brasileira de Estudos da Presença, 2023)
The São Vicente carnival is a symbol of the island’s identity and, at the same time, a field that evokes and intersects several identity referents, with Brazil being the main one. This article revisits the long history of discourses and representations about the identitarian relation between Cape Verde and Brazil, through the case of the São Vicente carnival. Based on archival and ethnographic research, the article presents several Brazilian cultural influences that over time marked the island’s carnival and discusses this supposed relation, proposing the mirror metaphor to better illustrate this unilateral identification and identity demand.